Fundamentals of Entrepreneurship (ENT300) : Sweet Scarf / Syahira Nadia Mohd Khairi - Mohd Khairi, Syahira Nadia (2020)
Sweet Scarf is business that produce high quality scarf for fulfill customers need. Sweet Scarf provide many types of scarf which are cotton, pashmina, satin and jersey. Customers easily attracts to the product in lower price but at the same time have a good quality. So, with this Sweet Scarf have made a scarf that will make customers satisfies with it.